Kumunism va khanivadah (Junbish-i Mustaqqil-i Zanan-i Irani dar Kharij az Kishvar)
Communism and the family. The title of this booklet has been inspired by Aleksandra Michajlovna Kollontaj's work of "communism and the family". The Persian translation of her work under the title of "Working woman and the mother" appears at the appendix.